SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN - Muhammad Khairul Halim, (UNISAN JURNAL, 2024)
The principal as a supervisor must be able to carry out supervision and control to improve the performance of educational staff. Supervision and control are controls so that educational activities run directed towards the set goals. Supervision and control are preventive measures to prevent educational staff from committing deviations and being more careful in carrying out their work. Apart from providing guidance and direction in improving teacher abilities, a supervisor must also provide motivation and control over teacher performance. This motivation aims to provide work enthusiasm to teachers, so that teachers will try to improve their performance. The implementation of the principal's academic supervision in improving the quality of learning consists of planning academic supervision, implementing academic supervision, evaluating academic supervision and following up on academic supervision. Keywords: Academic Supervision, Learning Quality